Technique notes on the management of superior sagittal or transverse sinus during the falcotentorial meningioma surgery: a case report - Liu, Jun; Fan, Di; Chen, Ligang; Zou, Zheng; Li, Xinning; Zhou, Minghao; Wen, Zhongcheng; Gong, Shun; Liang, Guobiao (Frontiers in Neurology, 2024)
Background: Falcotentorial meningiomas (FM) are surgical challenges for protecting sinus, and technique notes on the management of superior sagittal or transverse sinus are required for good results.Methods: We improved the technique notes on the management of superior sagittal or transverse sinus in 3 FM patients with signs of increased intracranial pressure or chronic headache.Results: All patients underwent surgeries in prone position, and occipital/sup-occipital/ sub-occipital craniotomy was performed. In 1 patient, the skull was removed traditionally with exposure of the confluens sinuum, superior sagittal and transverse sinus, while the longitudinal skull bridge was left to suspend the dura for protecting the superior sagittal sinus in 1 patient, and the transverse skull bridge was left to suspend the dura for protecting the transverse sinus in 1 patient. The dura was opened infratentorially or supratentorially to spare the sinus and then was suspend the "skull bridge". The tumor was then removed completely without brain swelling or significant venous bleeding.Complete tumor resection was confirmed by early postoperative imaging and all patients recovered well without postoperative morbidity.The authors recommend the "skull bridge" to suspend the dura for optimal control of the venous sinuses during the FM surgery (less venous bleeding).